Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans in umbilical cord and peripheral blood, saliva, colostrum from women with gingivitis (Research, Society and Development, 2021)
This study investigated and compared the presence of Porphyromonas gingivalis (Pg) and Aggregatibacter actinomycetemcomitans (Aa) in biological samples of women submitted to the term delivery diagnosed with gingivitis and healthy periodontium. Oral clinical exams were performed in 48 puerperal women including 28 women with healthy periodontium, 15 with gingivitis and 5 with periodontitis (that were excluded of analysis). Samples of umbilical cord blood (CB), peripheral blood (PB), saliva (SA) and colostrum (C) were collected from eligible women after delivery. DNA extraction was accomplished, and the presence of bacteria was detected by PCR with primers and specific probes for each microorganism. Data about previous and current pregnancies and known risk factors were obtained from patients’ medical records. Social, demographic, and oral care data was analyzed by interview. All salivas of participants with gingivitis presented Pg and Aa, while a minority of samples of with healthy periodontium had those bacteria (P